Magnetocaloric effect in a high-spin ferromagnetic molecular cluster - Agapaki, Eleftheria; Charkiolakis, Emmanouil K.; Nichol, Gary S.; Gracia, David; Evangelisti, Marco; Brechin, Euan K. (Frontiers in Chemistry, 2024)
The reaction of MnCl2·4H2O with HL ((1-methyl-1H-imidazol-2-yl)methanol) and pdH2 (1, 3 propanediol) in a basic MeCN solution results in the formation of a mixed-valence [Mn20] cationic cluster and two [MnIICl4] counter anions. The metallic skeleton of the cluster describes two geometrically equivalent mixed-valent, linked [MnIII6MnII4] supertetrahedra in which nearest-neighbor metal ions have a different oxidation state. Magnetic susceptibility, magnetization data and heat capacity measurements support evidence of predominant ferromagnetic correlations, leading to a s = 22 spin ground state for the [MnIII6MnII4] supertetrahedra, which are pair-linked by a weak antiferromagnetic coupling. The properties are discussed in the context of the magnetocaloric effect and the potential application of this compound in cryogenic refrigeration.